How Nonassociative Geometry Describes a Discrete Spacetime - Nesterov, Alexander I.; Mata, Héctor (Frontiers in Physics, 2019)
Nonassociative geometry, providing a unified description of discrete and continuum spaces, is a valuable candidate for the study of discrete models of spacetime. Within the framework of nonassociative geometry we propose a model of emergent spacetime. In our approach, the evolution of spacetime geometry is governed by a random/stochastic process. This leads to a natural appearance of causal structure and arrow of time. We apply our approach to study a toy model of discrete (2+1)-D spacetime and Friedmann-Robertson-Walker cosmological model. We show that in a continuous limit the evolution of the discrete spacetime corresponds to a radiation epoch of the standard cosmological model.